Effects of high EPA and high DHA fish oils on changes in signaling associated with protein metabolism induced by hindlimb suspension in rats - Marzuca-Nassr, G.; Vitzel, K.; De Sousa, L.; Murata, G.; Crisma, A.; Rodrigues Junior, C.; Abreu, P.; Torres, R.; Mancini-Filho, J.; Hirabara, S.; Newsholme, Philip; Curi, R. (2016)
© 2016 The Authors. Physiological Reports published by Wiley Periodicals, Inc. on behalf of the American Physiological Society and The Physiological Society.The effects of either eicosapentaenoic (EPA)- or docosahexaenoic (DHA)-rich fish oils on hindlimb suspension (HS)-induced muscle disuse atrophy were compared. Daily oral supplementations (0.3 mL/100 g b.w.) with mineral oil (MO) or high EPA or high DHA fish oils were performed in adult rats. After 2 weeks, the animals were subjected to HS for further 2 weeks. The treatments were maintained alongside HS. At the end of 4 weeks, we evaluated: body weight gain, muscle mass and fat depots, composition of fatty acids, cross-sectional areas (CSA) of the soleus muscle and soleus muscle fibers, activities of cathepsin L and 26S proteasome, and content of carbonylated proteins in the soleus muscle. Signaling pathway activities associated with protein synthesis (Akt, p70S6K, S6, 4EBP1, and GSK3-beta) and protein degradation (atrogin-1/MAFbx, and MuRF1) were evaluated. HS decreased muscle mass, CSA of soleus muscle and soleus muscle fibers, and altered signaling associated with protein synthesis (decreased) and protein degradation (increased). The treatment with either fish oil decreased the ratio of omega-6/omega-3 fatty acids and changed protein synthesis-associated signaling. EPA-rich fish oil attenuated the changes induced by HS on 26S proteasome activity, CSA of soleus muscle fibers, and levels of p-Akt, total p70S6K, p-p70S6K/total p70S6K, p-4EBP1, p-GSK3-beta, p-ERK2, and total ERK 1/2 proteins. DHA-rich fish oil attenuated the changes induced by HS on p-4EBP1 and total ERK1 levels. The effects of EPA-rich fish oil on protein synthesis signaling were more pronounced. Both EPA- and DHA-rich fish oils did not impact skeletal muscle mass loss induced by non-inflammatory HS.